Evaluation of small core-based specimens for characterization of stone deterioration. (April 2016) - Tiennot, Mathilde; Bourgès, Ann
Highlights: Evaluation of small diameter core-based specimen for toughness measurement. Adequate specimens and parameters for stone conservation purposes have been defined. The Semi-Circular Bending method is appropriate for cultural heritage studies.